Potencial de eficientização energética das micro e pequenas empresas comerciais varejistas de Santa Maria - Zancan, Marcos Daniel (2007)
This dissertation presents the energetic diagnostic of micro and small retail companies from Santa Maria-RS, allowing to identify the most important reasons of waste, energetic eficientization potential, as well as its impacts on the total electric power consumption. Therefore, energetic diagnostic allows the companies to define administration techniques, strategies and eficientization actions, as well as to determine the magnitude of the proposed actions results. Methodology used was based on expositive analysis from an exploratory research of technical reports from Critical Points Evaluation of the Energia Brasil Program, held in Santa Maria, during the year of 2003 and begining of 2004. Data was quantitatively broached, from statistic methods, whose results represent all the companies population on study. The results show the eficientization potential separated on technical topics (accounts and supplies, electric motors, air conditioning, artificial lighting, cooling and other equipments), as well as the total eficientization potential. Among the technical topics, artificial lighting has shown the biggest potential, followed by cooling, on both company types. The entire analysis, of all topics, for all the population of micro and small retail companies on study, identified high waste levels, reaching 13,5% for micro companies and 11,6% for small companies. These percentages represented a waste of electric power in excess of 13 millions of kWh/year, equivalent to 4,7 millions of R$/year. It was also verified that the investment return time for the energetic eficientization is low, reaching 7,1 months on micro companies and 8,2 months on small companies. This data shows the extend of the waste of electric power for the companies under this study as well as the large contribution that they can offer for a more efficient and smart employ of the electric power. For the companies, energetic eficientization is an important allied on the cost reduction of production as well as to the increase of quality and productivity of their products and/or services. This helps their competitivity, allowing their survival in the market. Therefore, micro and small companies have little knowledge about electric power, harming its administration, what makes them live peacefully with wastefullness